Traumatic rupture of the testicle - Golji, H.; Jaffar, D.J. (The American journal of surgery, 1957)
Traumatic rupture of the testis is described as a clinical entity. The importance of the following three points is emphasized: (1) In trauma of the scrotum, the possibility of rupture of the testis must be kept in mind. (2) Any accidental traumatic hematocele should be surgically explored. (3) The testis must be repaired with preservation of as much tissue as possible. The twenty-first case of traumatic rupture of the testis is reported.